Altered Functional Connectivity Between the Cerebellum and the Cortico-Striato-Thalamo-Cortical Circuit in Obsessive-Compulsive Disorder - Zhang, Haisan; Wang, Bi; Li, Kun; Wang, Xiaoyue; Li, Xianrui; Zhu, Jianli; Zhao, Qingjiang; Yang, Yongfeng; Lv, Luxian; Zhang, Meng; Zhang, Hongxing (Frontiers in Psychiatry, 2019)
Background: Structural and functional neuroimaging studies have indicated that the cortico-striato-thalamo-cortical (CSTC) circuit contributes to the pathophysiology of obsessive compulsive disorder (OCD). Recent research shows that the cerebellum has extensive communication with the regions in the CSTC circuit, such as the striatum, thalamus, and cingulate. However, the functional connectivity between cerebellum and CSTC circuit in patients with OCD under resting state has not been demonstrated. Methods: Thirty patients with OCD and twenty-six age and sex matched healthy controls (HC) were included in the study. ALL patients were scored using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). All participants were collected functional resting magnetic resonance data, and calculate the whole brain of fractional amplitude of low frequency (fALFF) value. An independent sample T test was used to compare the differences between the two groups. In addition, regions showing differences between OCD patients and HC were selected as region of interest (ROI) for whole brain-based functional connectivity (FC) analysis. Correlation analysis was used to analyze the relationship between Y-BOCS score and fMRI data. Results: Compared with the HC group, OCD group showed significantly increased mfALFF value in Crus II region, Lobule VIII region on the left side and Lobule VIII region on the right side. The mfALFF values in the Crus II region of the cerebellum was positively correlated with the Y-BOCS total scores. The results of FC analysis showed weakened between left Crus II and the right dorsal striatum and ventral striatum, the left Lobule VIII and the right dorsal striatum, and between the right Lobule VIII and the right dorsal striatum and right anterior cingulate in OCD, compared to HC. The FC values between left Crus II and right dorsal striatum were negatively correlated with Y-BOCS total scores. Conclusions: Region of the bilateral inferior cerebellar (Crus II and Lobule VIII) of the OCD patients showed increased activation and decreased weakened FC with the CSTC circuit (right striatum and right cingulate). And the above results were related to the severity of clinical symptoms of patients. Suggesting that abnormal connection between cerebellum and CSTC circuit may be involved in the neuropathology of OCD.